2014
DOI: 10.4149/bll_2014_037
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia – the most common complication after total thyroidectomy

Abstract: Abstract:Objectiva: Postoperative intact parathyroid hormone (iPTH) levels and some other factors as a predictor of hypocalcemia are analyzed in 115 patients after TTE. Background: Postoperative hypocalcemia is the most common complication observed after total thyroidectomy (TTE). It is not easy to predict in which patients this complication will occur. We adopted and implemented a novel method to predict this complication -monitoring of postoperative intact parathyroid hormone (iPTH) levels. Methods and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Current methods are based on measurement of calcium and PTH levels at different time points, with early (a few minutes to 12 h after thyroid resection) PTH measurements reliably predicting the absence of hypoparathyroidism. Other authors have suggested using quick PTH measurements, which could also help the surgeon decide whether or not to autotransplant a parathyroid gland.…”
Section: Introductionmentioning
confidence: 99%
“…Current methods are based on measurement of calcium and PTH levels at different time points, with early (a few minutes to 12 h after thyroid resection) PTH measurements reliably predicting the absence of hypoparathyroidism. Other authors have suggested using quick PTH measurements, which could also help the surgeon decide whether or not to autotransplant a parathyroid gland.…”
Section: Introductionmentioning
confidence: 99%
“…The current techniques for evaluating parathyroid function are based on calcium (25,26) and PTH (6,27-31) measurements at various time points during or after thyroidectomy. Some studies have suggested that early (a few minutes to 12 hours after thyroid resection) PTH measurements reliably predict the absence of hypoparathyroidism, with a positive predictive value up to 97% (6,27,28). However, this finding has been challenged by other authors (32,33).…”
Section: Fluorescent Techniques With Icg In Neck Surgerymentioning
confidence: 41%
“…These results were comparable to the studies conducted in past. [23,24] Postoperative other complications among all cases were seroma, transient hoarseness of voice and neck hematoma. [25,26] Shortly after surgery, hypocalcemia is a common occurrence.…”
Section: Hypocalcemiamentioning
confidence: 95%